Fox (Vulpes vulpes) involvement identified in a series of cat carcass mutilations. Issue 2 (March 2022) - Hull, Kita D.; Jeckel, Sonja; Williams, Jonathan M.; Ciavaglia, Sherryn A.; Webster, Lucy M. I.; Fitzgerald, Ella; Chang, Yu-Mei; Martineau, Henny M.
This study was designed to identify the cause of mutilation and death in 32 cats, part of a larger cohort found dead in Greater London, the United Kingdom, between 2016 and 2018. At the time, discussion in the media led to concerns of a human serial cat killer (dubbed The Croydon Cat Killer) pursuing domestic cats, causing a state of disquietude. Given the link between animal abuse and domestic violence, human intervention had to be ruled out. Using a combination of DNA testing, computed tomography imaging, and postmortem examination, no evidence was found to support any human involvement. Instead, a significant association between cat carcass mutilation and the presence of fox DNA was demonstrated. Gross examination identified shared characteristics including the pattern of mutilation, level of limb or vertebral disarticulation, wet fur, wound edges with shortened fur, and smooth or irregular contours, and marks in the skin, muscle, and bone consistent with damage from carnivore teeth. Together these findings supported the theory that the cause of mutilation was postmortem scavenging by red foxes ( Vulpes vulpes ). The probable cause of death was established in 26/32 (81%) carcasses: 10 were predated, 8 died from cardiorespiratory failure, 6 from blunt force trauma, one from ethylene glycol toxicity, and another from liver failure. In 6 carcasses a cause of death was not established due to autolysis and/or extensive mutilation. In summary, this study highlights the value of a multidisciplinary approach to fully investigate cases of suspected human-inflicted mutilation of animals.